IDENTIFICATION, ASSESSMENT AND MAPPING OF ECOSYSTEM SERVICES IN THE CONTEXT OF SUSTAINABLE NATURAL RESOURCE MANAGEMENT - Pelyukh, Oksana (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The growing “polycrisis”, characterised by environmental degradation, climate change and resource scarcity, further exacerbated by the war in Ukraine, highlights the urgent need for sustainablenatural resource management. Despite the extensive development of the ecosystem services concept, a significant gap remains between scientific knowledge and its integration into decision-making processes.This study aims to develop a theoretical and methodological approach to integrating ecosystem service values into decision-making by identifying, assessing, and spatially mapping them. The proposedapproach combines economic valuation and GIS-based analysis to generate spatially explicit outputs and support evidence-based environmental policy and sustainable post-war recovery.